Does high‐resolution modelling improve the spatial analysis of föhn flow over the Larsen C Ice Shelf?. (3rd July 2017) - Turton, J. V.; Kirchgaessner, A.; Ross, A. N.; King, J. C.
Abstract : The ice shelves on the east coast of the Antarctic Peninsula (AP) have been disintegrating for over two decades. Surface melting induced by föhn winds has been proposed as a driver of this disintegration. Föhn winds are adiabatically warmed dry winds, formed by the interaction of a mountain range with perpendicularly approaching winds, in this case of the AP mountains with the prevailing circumpolar westerlies. Assessing their impact is difficult due to the sparsity of observations and the relatively low‐resolution of operational forecasts. We have carried out high‐resolution simulations using the Weather Research and Forecasting (WRF) model to provide more detailed simulations of the spatial distribution of the föhn air. The analysis presented here covers the period from 10 to 22 May 2011 and focuses on two föhn events during this period. Results show that a stable boundary layer can reduce the impact of föhn, as can the occurrence of cooler föhn jets. Abstract : Föhn winds over the Larsen C Ice Shelf have been simulated as a case study from May 2011 using the Weather Research and Forecasting (WRF) model at both 5 and 1.5 km horizontal resolution. In the higher‐resolution simulation, the spatial distribution of the warm, dry föhn air is more accurately simulated than in the lower‐resolution run. Understanding the spatial extent of the föhn air is crucial for estimating the impacts on the ice shelf surface.